Urang Cave Karst Environmental Development, as Tourism Object - Srijono, Srijono; Nadia, Nisa (Forum Geografi, 2013)
Karst environment become an alternative tourist destination as well as to boost local revenues. In karst environments in Grobogan District, Central Java Province, formed Urang Cave, with an interesting endokarst phenomenon. This study aims to do zoning district Urang Cave as tourist sites. The research method is using contour maps as a base map of Urang Cave karst environment geomorphological mapping. Geomorphological data processing is using ArcView GIS 3.3 program. Land use map refers to RBI, scale 1:25.000. Geomorphological analysis refers to the Ministry of Energy and Mineral Resources No. 1456.K/20/MEM/2000, and petrography. Each development zone is analyzed its geophysical environmental element, then set scoring and value summation. For comprehensive environmental element analysis, chemical analysis of rocks, and water-soil chemistry. In reference to Minister of Energy Mineral Resource decrees No. 1456/K/20/MEM/2000, Urang Cave zoning defined into 3 (three) zone, as follow: the Protected Zone, Cultivation Zone 1, and Cultivation Zone 2. Protected Zone, consists of Urang Cave tunnel/hallway with a unique spheleothem in it. This zone as a cave tracking site tourism, potential to produce karst water as a decent drinking water while maintaining hardness. Cultivation Zone 1 is spreading about 200 m in distance from outer appearance of spring around the cave hallway. In this zone mining of cave sediments may be done in the inactive form caves, without changing the state of the existing major exokarst morphology. Cultivation Zone 2, an outer zone, located farthest from the tunnel/hallway Urang Cave. Utilization of this zone as a limestone mining quarry, although only on a small scale.